Seeds of conflict, seeds of compromise: A historiography of American workers and adult education in the first half of the twentieth century - Fred M. Schied; Kenneth C. Welensky (Adult Education Research Conference, 1996)
This paper reviews three interpretive schemes for understanding workers’ education, then highlights federal and university involvement. The study reviews some of the major critiques of workers’ education, highlighting workers’ education often ambiguous and contradictory nature.